02 Mitochondrial DNA damage, dysfunction and atherosclerosis. Issue 24 (24th November 2011) - Yu, E; Mercer, J; Figg, N; Bennett, M
Abstract : Rationale: Atherosclerosis remains the leading cause of death in the western world. Mitochondrial DNA (mtDNA) damage has been associated with the disease, but it is unknown when the damage occurs relative to atherogenesis, and what the functional and clinical consequences are. Methods: To assess the role of mtDNA damage in atherosclerotic development, we studied its time course, by quantifying the abundance of oxidative adducts and the 4977 base pair "common" deletion. We further examined respiratory chain complex expression and function in apolipoprotein E null mice. Results: We identified that aortic tissues have oxidative lesions of mtDNA at the early stages of atherogenesis, while the common 4977 base pair deletion was increased in established plaque. Despite normal respiratory complex expression, isolated mitochondria showed reduced complex I activity, which correlated with advanced atherosclerosis. Conclusions: We confirm that mtDNA damage is present in the early stages of atherogenesis and may be contributive to disease. We also identified a respiratory chain defect which may compromise the bioenergetic capacity of the cells, leading to increased plaque vulnerability.